A double pressure to perform? Pupils talk about grades and parents in a multicultural school setting in Sweden. Issue 1 (2nd January 2022) - Löfgren, Håkan; Aman, Robert
ABSTRACT: The aim is to contribute knowledge about the ways in which Swedish pupils with a migrant background speak about school performances and their first experiences of being graded. The results describe pupils and parents as positioned as being lower down in a top-down relationship vis-à-vis school. The separation between home and school is best described as robust. Some pupils want and ask for a better school-home relationship because they think it would harmonise the relationship with their parents and facilitate their school work. The main conclusion is that pupils find themselves in a vulnerable position between schools'/teachers' demands and parents' aspirations for them.